Computational fluid dynamics simulation as a tool for optimizing the hydrodynamic performance of membrane bioreactors. Issue 55 (9th October 2019) - Jin, Yan; Liu, Cheng-Lin; Song, Xing-Fu; Yu, Jian-Guo
Abstract : The hydrodynamic properties and shear stresses experienced by a membrane bioreactor (MBR) are directly related to its rate of membrane fouling. Abstract : The hydrodynamic properties and shear stresses experienced by a membrane bioreactor (MBR) are directly related to its rate of membrane fouling. In this study, computational fluid dynamic models have been combined with cold model PIV experimental studies to optimize the performance properties of MBRs. The effects of membrane module height, number of aeration tubes and membrane spacing on liquid phase flow rates, gas holdup and shear stresses at the membrane surface have been investigated. It has been found that optimal MBRs experience the greatest shear forces on their surfaces at a distance of 250 mm from the aeration tube, around the 7 aeration tubes used to introduce gas and at the 40 mm spacings between the membrane sheets. Use of an aeration intensity of between 0.02 and 0.47 m 3 min −1 generated shear stresses that were 50–85% higher than the original MBR for the same aeration intensity, thus affording optimal membrane performance that minimizes membrane fouling.